"I Didn’t Sign Up for This!": Informed Consent in Social Network Research - Hutton, Luke; Henderson, Tristan (Proceedings of the International AAAI Conference on Web and Social Media, 2021)
The issue of whether, and how, to obtain informed consent for researchstudies that use social network data has recently come to the fore insome controversial cases.Determining how to acquire valid consent that meets the expectations of participants, while minimising the burden placed on them, remains an open problem.We apply Nissenbaum’s model of contextual integrity to the consent process, to study whether social norms of willingness to share social network data can be leveraged to avoid burdening participants with too many interventions, while still accurately capturing their own sharing intent. We find that for the 27.7% of our participants (N = 109) who conform to social norms, contextual integrity can be used to significantly reduce the time taken to capture their consent, while still maintaining accuracy. Our findings have implications for researchers conducting such studies who are looking to acquire informed consent without having to burden participants with many interactions.